2022
DOI: 10.3390/cancers14133077
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multiprotein Classifier for the Detection of Early Stage Ovarian Cancer

Abstract: Background: Individual serum biomarkers are neither adequately sensitive nor specific for use in screening the general population for ovarian cancer. The purpose of this study was to develop a multiprotein classifier to detect the early stages of ovarian cancer, when it is most treatable. Methods: The Olink Proseek Multiplex Oncology II panel was used to simultaneously quantify the expression levels of 92 cancer-related proteins in sera. Results: In the discovery phase, we generated a multiprotein classifier t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…As a potential solution to the lack of specificity of the upregulated miRNAs, this study also identified four miRNAs (miR-486a-3p/5p and miR-486b-3p/5p) that were in lower abundance in the EVs secreted from ovaries of 3-month Fancd2 -/mice and exhibited reduced expression in micro-dissected sex cords and tubulostromal adenomas. Even though upregulated biomarkers are more likely to be detectable in the circulation, it is not unrealistic to utilise the lack of a biomarker for a diagnostic panel, as is the case for the Proseek Multiplex Oncology Panel II [325]. Therefore, the absence of these miRNAs are also potential unique biomarkers that are not deficient in EVs at later stages, but are representative of the tumour tissue, thus are potential unique early ovarian cancer markers in this model.…”
Section: Candidate Secreted Biomarkers Of Eoc In the Fancd2 Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As a potential solution to the lack of specificity of the upregulated miRNAs, this study also identified four miRNAs (miR-486a-3p/5p and miR-486b-3p/5p) that were in lower abundance in the EVs secreted from ovaries of 3-month Fancd2 -/mice and exhibited reduced expression in micro-dissected sex cords and tubulostromal adenomas. Even though upregulated biomarkers are more likely to be detectable in the circulation, it is not unrealistic to utilise the lack of a biomarker for a diagnostic panel, as is the case for the Proseek Multiplex Oncology Panel II [325]. Therefore, the absence of these miRNAs are also potential unique biomarkers that are not deficient in EVs at later stages, but are representative of the tumour tissue, thus are potential unique early ovarian cancer markers in this model.…”
Section: Candidate Secreted Biomarkers Of Eoc In the Fancd2 Modelmentioning
confidence: 99%
“…Interestingly, many multivariate serum protein assays focus on markers that are upregulated in cancer patients over controls. However, recently an adaptation of the Oncology II panel studied the specificity and sensitivity of a biomarker panel with CA-125 and HE4 that also included serum proteins, integrin subunit alpha V (ITGAV) and seizure related 6 homolog like (SEZ6L), which are significantly downregulated in all epithelial subtypes of Stage I and II OC [325]. However, even with the proliferation of multivariate protein serum diagnostic panels targeted toward earlier OC detection, they have yet to be rigorously tested and made available for clinical use.…”
Section: Current Biomarkers Of Epithelial Ovarian Cancermentioning
confidence: 99%